Regulation of mitochondrial dysfunction induced cell apoptosis is a potential therapeutic strategy for herbal medicine to treat neurodegenerative diseases - Li, Ruo-Lan; Wang, Ling-Yu; Duan, Hu-Xinyue; Zhang, Qing; Guo, Xiaohui; Wu, Chunjie; Peng, Wei (Frontiers in Pharmacology, 2022)
Neurodegenerative disease is a progressive neurodegeneration caused by genetic and environmental factors, and Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD) are the three most common neurodegenerative diseases clinically. Unfortunately, the incidence of neurodegenerative diseases is increasing year by year, however, the current available drugs have poor efficacy and large side effects, which brings a great burden to the patients and the society. Increasing evidence suggests that neurodegenerative disease occurrence is closely related to mitochondrial dysfunction, which can affect mitochondrial biogenesis, mitochondrial dynamics, as well as mitochondrial mitophagy. Through the disruption of mitochondrial homeostasis regulation, nerve cells undergo varying degrees of apoptosis. Interestingly, it has been shown in recent years that the natural agents extracted from herbal medicine are beneficial for prevention/treatment of neurodegenerative diseases via regulation of mitochondrial dysfunction with less side-effects. Therefore, in this review, we will focus on the potential therapeutic agents from herbal medicine for treating neurodegenerative diseases via suppressing apoptosis through regulation of mitochondrial dysfunction, in order to provide a foundation for the development of these anti-neurodegenerative disease drugs from herbal medicine.